A Study on Puncture Resistance of Composite Metal Foam Core Sandwich Panels. Issue 12 (23rd August 2020) - Rabiei, Afsaneh; Portanova, Marc; Marx, Jacob; Scott, Christopher; Schwandt, Jerod
Abstract : Steel–steel composite metal foam‐core sandwich panels (S‐S CMF‐CSP) with variety of thicknesses of components (face sheets and cores) are manufactured by attaching stainless steel face sheets to a S‐S CMF core using either solid‐state diffusion bonding or adhesion bonding. Scanning electron microscope imaging is used to evaluate the microstructure of diffusion bonded panels particularly at the interface of the core and face sheets. The puncture resistance of the sandwich panels is evaluated using a 0.50 caliber Mann gun barrel, modified to fire 2.54 and 3.175 cm diameter steel balls creating kinetic puncture energies up to 14 500 J. But, no complete penetrations through any of the sandwich panels are achieved. At lower impact velocities, tensile stresses resulted from the sudden changes in mechanical impedance between various layers of the sandwich panel recoil the ball back while at higher impact velocities, the high strain rate deformation at the point of impact along with the friction heat between the ball and panel surface fuses the ball to the target instantly resulting in debonding of adhesively bonded panels, whereas the diffusion bonded panels resist better. Sandwich panels with higher areal densities and thicker face sheets did not show major advantages over the panels with thinner face sheets. Abstract : Steel–steel composite metal foam core sandwich panel (S‐S CMF‐CSP) tiles are impacted using steel balls with 488–14 500 J puncture energies over 5.06–7.91 cm 2 impact areas. Due to the high energy absorption of the S‐S CMF core in compression and that of the face sheets in tension, none of the panels show a complete penetration through their thickness.